2022
DOI: 10.3390/ijms232113277
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in High-Risk Early-Stage Colorectal Cancer—Its Clinical and Biological Significance in Immune Microenvironment

Abstract: Programmed death-ligand 1 (PD-L1) is an immune checkpoint molecule that can regulate immune responses in the tumor microenvironment (TME); however, the clinical applications of PD-L1 in early-stage colorectal cancer (CRC) remain unclear. In this study, we aimed to investigate the relationship between PD-L1 expression and survival outcome and explore its relevant immune responses in CRC. PD-L1 expression was evaluated by immunohistochemical staining to determine the tumor proportion score and combined positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…It should be emphasized that these results should be interpreted in the context of all other factors, such as intrinsic MMR status, microsatellite instability, the existence of intratumoral immune cells, the tumor burden of gene mutations (clonality, aneuploidy, and classes of mutations), and extrinsic factors, such as the microbiome. The patient would benefit from their application [5,15,[24][25][26][27]. Immunotherapy is certainly not harmless and has harmful consequences; still, the need for radical surgical procedures could be significantly reduced, as could the severe toxic effects of neoadjuvant chemotherapy with fluoropyrimidine and oxaliplatin, such as intestinal, urinary, and erectile dysfunction, infertility, and sensory neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that these results should be interpreted in the context of all other factors, such as intrinsic MMR status, microsatellite instability, the existence of intratumoral immune cells, the tumor burden of gene mutations (clonality, aneuploidy, and classes of mutations), and extrinsic factors, such as the microbiome. The patient would benefit from their application [5,15,[24][25][26][27]. Immunotherapy is certainly not harmless and has harmful consequences; still, the need for radical surgical procedures could be significantly reduced, as could the severe toxic effects of neoadjuvant chemotherapy with fluoropyrimidine and oxaliplatin, such as intestinal, urinary, and erectile dysfunction, infertility, and sensory neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PD-L1 has been proposed as a prognostic biomarker in colorectal cancer; still, it has not yet been put into practice because the evaluation of immunohistochemical analysis, the scoring method, and the application of different types of immunohistochemical tests, materials, and patient screening are not standardized [5].…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the expression of this pathway may help in indication of check point inhibitor therapy. Furthermore, recent studies [24] revealed that PD-L1 expression in CRC TME is a directly correlated with the recurrence-free survival and related with cancer-associated immune responses such as: IFN-gamma response, IL-2-STAT5 signalling and the IL-6-STAT3 signalling pathway, which makes it a valuable prognostic marker in early-stage CRC.…”
Section: Pd-1/ctla-4 Receptors Expressionmentioning
confidence: 99%
“…The molecular classification of CRC can be based on immunohistochemical and molecular biomarkers, such as keratins 7 and 20 and BRAF (v-raf murine sarcoma viral oncogene homolog B1) gene status, which can be used to identify serrated carcinomas [ 6 ] or maspin, E-cadherin, ß-catenin, and vimentin, which can be used to assess the epithelial–mesenchymal phenomenon [ 2 ]. Markers of microsatellite instability, including immune checkpoint molecules, such as programmed death-ligand 1 (PD-L1) and KRAS (v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog) gene status, may be helpful to determine the best oncological approach [ 1 , 2 , 4 , 7 ].…”
mentioning
confidence: 99%
“…To enable this, immune checkpoint inhibitors should be combined with vaccines against immunogens and adoptive cell therapy [ 18 ]. Chung et al proposed the simultaneous therapeutic inhibition of PD-L1 and its triggers based on the interaction of PD-L1 with genes that regulate the tumor microenvironment, such as Chemokine (C-X-C motif) ligand 9 (CXCL9) [ 7 ].…”
mentioning
confidence: 99%